2014
DOI: 10.3389/fneur.2014.00117
|View full text |Cite
|
Sign up to set email alerts
|

Upper Limb Function and Cortical Organization in Youth with Unilateral Cerebral Palsy

Abstract: Aim: To explore the relationship between motor cortical and descending motor pathway reorganization, lesion type, and upper limb function in youth with unilateral cerebral palsy (CP).Methods: Twenty participants with unilateral CP (mean age 15 ± 3 years; 11 males) completed a range of upper limb functional measures. Structural MRI, diffusion-weighted, and functional MRI were conducted to determine type and extent of brain lesion, descending white matter integrity, and whole-brain activity during affected hand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 42 publications
2
44
1
2
Order By: Relevance
“…Bilateral brain damage in children with unilateral CP has been previously reported although frequencies were highly variable. 6-8, 10 Correlations between the contralesional global scores and AHA performance were not significant for both groups. This is in line with Holmefur et al, 9 who already reported the lack of impact of bilateral abnormalities on UL function.…”
Section: Accepted Manuscriptmentioning
confidence: 80%
“…Bilateral brain damage in children with unilateral CP has been previously reported although frequencies were highly variable. 6-8, 10 Correlations between the contralesional global scores and AHA performance were not significant for both groups. This is in line with Holmefur et al, 9 who already reported the lack of impact of bilateral abnormalities on UL function.…”
Section: Accepted Manuscriptmentioning
confidence: 80%
“…These characteristics could possibly have influenced their response to treatment. In future studies, with the availability of brain imaging techniques (Krageloh-Mann & Horber, 2007;Scheck, Boyd, & Rose, 2012) and knowledge of the relationship between specific brain lesions, corticomotor projection patterns, and hand function (Arnfield, Guzzetta, & Boyd, 2013;Feys et al, 2010;Holmstrom et al, 2010;Mackey, Stinear, Stott, & Byblow, 2014), UL interventions may be better tailored to the neurological characteristics of individual patients.…”
Section: Discussionmentioning
confidence: 98%
“…Distinct changes in activation patterns have been reported in rehabilitative studies of adult stroke (postrehabilitation versus retention), 111 hemispherectomy (pre-versus postrehabilitation), 125 and paediatric CP (preversus postrehabilitation), 66 despite subjects demonstrating stable motor scores. In unilateral CP, the degree of S1M1 activation for active and passive movements may not correlate with motor scores, 105,113 and results for sensory impairment are mixed. 57,105,126 Similarly, for stroke, activation of the ipsilateral primary motor cortex has been associated with both good and poor behavioural outcomes.…”
Section: T-fmri Results Are Variablementioning
confidence: 99%
“…112 Both stroke and unilateral CP patients, however, regularly demonstrate robustly bilateral activation. 105,113,114 These balances of activation are typically calculated as laterality index (LI):…”
Section: Laterality Shiftsmentioning
confidence: 99%